Peningkatan Prestasi Belajar Matematika Siswa Kelas IV SD 4 Adiwarno Melalui Metode Guided Discovery Learning - Junianti, Mamik (Universitas Sebelas Maret, 2020)
research was motivated by the problem of the low learning outcomes of fourth grade mathematics. This is because mathematics learning is still teacher centered or still dominated by teachers, teachers tend to still teach mathematics in an abstract/symbolic way where the learning method is contrary to the cognitive development of students. This study aims to determine whether there is an increase in mathematics learning outcomes using the Guided Discovery Learning method in fourth grade students of SD 4 Adiwarno. The research was conducted in March-April 2020 in the fourth grade of SD 4 Adiwarno, Mejobo District, Kudus Regency as the research subject. The results of the study showed that the results of learning mathematics in the initial conditions were only 33.33% of students who reached the KKM. There was an increase in the first cycle of learning outcomes to 50% of students and in the second cycle increased to 94.4% of students who reached the KKM. The author suggests elementary school teachers to apply the Guided Discovery Learning method in learning mathematics in order to improve student achievement.